Implementation of Duties and Authorities of Sabhara Police on Demonstration - Cahaya Mutiara Mardiana Putri; Arpangi Arpangi (Law Development Journal, 2020)
. Demonstration activities are actually a form of human rights protected by law, in realizing the will of citizens in expressing opinions freely, they must be maintained, so that the entire institutional social order is protected from deviations or violations of the law and can guarantee a sense of security in people's lives. Smoothly, orderly and safely in accordance with the objectives of the demonstration. Police are law enforcement officers who are directly dealing with this matter, so this research examines the duties and authorities of the police in handling demonstrations in the title. The implementation of duties and powers of the Sabhara police unit in handling demonstrations in accordance with the police law. This study uses a sociological juridical approach. The conclusion of this study is that the authority and police units of the Sabhara in handling demonstrations are not specifically stated in the law Indonesian National Police, however, it states the general powers of the police namely maintaining security and public order, enforcing the law, and providing protection, protection and services to the community in order to maintain security.